'Care-ful' boundary negotiation: Curating translocal subjectivities among Japanese women in London. (November 2022) - Takahashi, Kaoru
Abstract: This paper explores the everyday experience of Japanese female migrants in London. Asking how culture can offer us a lens through which to understand the diversity and heterogeneity of care in this globalised world, the Japanese concept of omoiyari, as curation of landscapes of care, is used as an analytical lens to unpack the interplay between culture, care and identity, illuminating the boundary-drawing aspects of ethics of care with which people make ongoing distinctions between self and others, and constructing translocal subjectivities. Understanding care as a form of communication, this paper uncovers the contextual and relational formation of care and self, and how this is enabled as well as constrained by culture. It contributes to an understanding of the relational formation of care in which caring practice is neither static nor embedded in place and culture, but is rather shaped through relationships dynamically, while social relationships in turn also shape the meaning of care. Highlights: This ethnographic study on Japanese female migrants in London unpacks the interplay among culture, care and identity. It highlights omoiyari as a cultural value in the negotiation of Japanese migrant women's everyday social relations. The Japanese migrant women make ongoing negotiations about the boundaries of landscapes of care with intimate others. Omoiyari as a curation of care offers a cultural analytical lens to explore the mutuality of care.